DEN INNOVATIVE IDEOLOG I POLITISK HISTORIE MOGENS GLISTRUP SOM CASE - Sørensen, Michael Kuur (Temp - tidsskrift for historie, 2014)
ABSTRACT The Innovative Ideologist in Political History: Mogens Glistrup as Case In this article it is shown, both qualitatively and quantitatively, how Quentin Skinners concept of the innovative ideologist can be of use for traditional political history. Skinner’s concept of the innovative ideologist directs attention to three ways in which an actor can marshal legitimacy to policies that are not generally accepted in a contemporary setting. The 􀏐irst is to create a new set of political slogans, words or concepts that supports the political program of the actor. The second is to re-describe concepts in a way that is congenial to the actor’s political program. The third way is to show that the policies the actor proposes will lead to outcomes that are generally seen as positive/morally desirable in the context. By means of an example from Danish political history the article shows how the right wing populist, Mogens Glistrup, attempted to legitimate his policies in the 1970s with the use of these strategies. For traditional political history this actor has been given a marginal role in Danish politics. This article shows how an actor like Mogens Glistrup becomes an interesting figure for historical research when directing attention to the way in which he tried to legitimate his policies in an unfavorable political environment.